The Characteristics of Natural Killer Cells and T Cells Vary With the Natural History of Chronic Hepatitis B in Children - Yingzhi Zhou; Yingzhi Zhou; Yi He; Yi He; Yunan Chang; Yunan Chang; Xiaorong Peng; Xiaorong Peng; Ruiqiu Zhao; Ruiqiu Zhao; Mingli Peng; Peng Hu; et al. (Frontiers Media S.A., 2021)
Background and Aims: The immune status of children with chronic hepatitis B (CHB) in different phases is still unclear. The aim of this study was to investigate the phenotype and cytokine-producing ability of natural killer (NK) and T cells and to better understand the immune characteristics of children with different phases of CHB.Methods: Treatment-naive children with CHB were divided into groups with different clinical phases of CHB. Fresh peripheral blood drawn from hepatitis B virus (HBV)-infected and healthy children was processed to perform flow cytometric analysis.Results: A total of 112 treatment-naive children with CHB and 16 comparable healthy controls were included in this study. The expression of HLA-DR on NK cells and CD38 on T cells were upregulated, especially in the IA phase, in children with CHB compared with healthy controls. The ability of circulating NK cells instead of CD8+ T cells to produce IFN-γ in children with CHB was slightly increased, but TNF-α production seemed to be decreased compared with that in healthy controls. The expression of some activation markers varied among children with different phases of CHB, especially the higher CD38 expression found on T cells in the IA phase. Regression analysis revealed that IFN-γ and TNF-α production by NK cells and CD8+ T cells seemed to have positive correlations with ALT elevation and an activated status of NK cells or T cells.Conclusion: NK cells and T cells tended to be phenotypically activated (especially in the IA phase) in children with CHB compared with healthy controls. However, their cytokine-producing function was not obviously elevated, especially IFN-γ production by CD8+ T cells. More studies investigating the mechanism and observing the longitudinal changes in the immune status in children with CHB are needed.